The Culture, the Council, and the Really Important Sideshow: An Experiment in History and Historiography - Heever, Gerhard van den (Religion & theology, 2025)
This essay surveys the dominant commentaries and discourses on the Council of Nicaea and the Nicene Creed, and proceeds to critique contemporary Nicene-derived and -inspired theological thinking which constructs its meaning to reside solely in the theological discourses associated with and clustering around the Council and its Creed. Through critical historiography and theories of discourse, the history of the Council and the Creed is read as a discursive formation the meaning of which lies outside of the Nicene disputation. By setting "Nicaea" as icon within the framework of changes in religious mentalities of the period, the rising cults of saints and martyrs, the article argues that the Council of Nicaea was actually conceived as the vicennalia, the celebration of Constantine’s rule, especially his victory over Licinius, and that the real prize for Emperor Constantine was the erection of the Church of the Holy Sepulchre. The Church was celebrated as a monument to Constantine’s victory, and the celebrated Nicene formula of homoousios helped link Constantine to Christ as a means to authorise his rule.